MICROLECTURE/LAB HYBRID CLASS FOR BRIDGING THE GAP BETWEEN THEORIES AND APPLICATIONS IN TEACHING ENGINEERING SUBJECTS - Muhsan, Ali Samer; Albarody, Thar M. Badri (Platform, a Journal of Engineering, 2019)
There is a paradigm shift taking place in the academy, in which the focus is moving from faculty, their teaching to learners and their learning. Efforts to improve the learner’s learning include a variety of innovative pedagogical approaches (such as first-year design courses, cooperative learning, problem base learning, technology-enhanced education, and distance learning). As engineering educators are leading the way in many of these areas, it is also important to recognize the role of learners in this transformation process. Most engineering lecturers who teach engineering mechanics, especially Statics and Dynamics are used to teach this subject in a theoretical manner. This research suggests a teaching method that could reduce or eliminate the gap between theories and applications in teaching engineering mechanical subjects through achieving a lecture/lab hybrid classroom environment where a portable lab illustration along with micro lecture method is implemented for learners’ engagement (learners-centered learning) and better teaching technique that covers both the visual/practical and the auditory/theory learning styles. In the micro lecture, the lecturer is available for learners at home through videos or internet-based lectures and class time is used to complete assignments by moving the instruction to the homework to the class. Learners are given more ‘one-on-one’ time with their lecturer to work their assignments and the role of the academic staff changes from a lecturer to an instructor. During class time, the portable lab toolkits are used to illustrate the main concepts of the given subject further. The instructor asks the learners to start an experiment by discussing with their peers and make a prediction of the outcome of that experiment. Thus, the learners’ preconceptions relevant to the phenomenon are studied. Secondly, learners perform the experiment and are asked to compare the outcome and prediction. If the outcome and prediction did not match, they would have to reflect on their observations. Keywords: Portable lab, Flipped classroom, Technology-enhanced education, Problem based learning, Cooperative learning